Development of batwan (Garcinia binucao) fruit for general culinary utilization. - Jamora, Annie Lyn Abuhin
Batwan fruit (Garcinia binucao) is an underutilized fruit but with high potential to be preserved for general culinary utilization. Batwan was fermented in 6.25%, 12.50% and 18.75% brine concentrations for 1, 2, and 3-week fermentation periods. The effect of brine concentrations and fermentation periods was analyzed through physico-chemical analyses such as pH, total soluble solids and percent titratable acidity (%TA). The proximate analyses such as salinity and specific gravity determination were also determined. The sensorial characteristics (color, texture, and taste) and overall acceptability of fermented batwan were evaluated. The physico-chemical analyses revealed that the brine concentrations and fermentation periods have no significant interactions. The pH was inversely proportional with the brine concentrations. On the other hand, the TSS and %TA were directly proportional with the brine concentrations. The salinity and the specific gravity of brine solutions were directly proportional to the brine concentration. The specific gravity was decreased at the end of fermentation period. Two-Way Analysis of Variance at P-value of 0.05 revealed that there was no significant difference on the pH of fermented batwan. The TSS differed significantly on the different brine concentrations used. The %TA values had a significant difference on different fermentation periods. The Friedman test showed that the specific attributes (color, texture and taste) for sensory evaluation did not vary significantly among the different formulations. The overall acceptability values ranged from 3.96 (least acceptable) to 6.25 (most acceptable) which was perceived as dislike slightly, respectively.